Combined in-depth X-ray Photoelectron Spectroscopy and Time-of-Flight Secondary Ion Mass Spectroscopy study of the effect of deposition pressure and substrate bias on the electrical properties and composition of Ga-doped ZnO thin films grown by magnetron sputtering - Correia, Filipe Costa (2018)
This work reports the effect of the applied substrate bias and deposition pressure on the bulk composition, electrical and microstructural properties of Gallium-doped Zinc Oxide thin films deposited by DC magnetron sputtering. In-depth Time-of-Flight Secondary Ion Mass Spectrometry and X-ray Photoelectron Spectroscopy studies were endured to determine the Ga content for the varying process conditions. Experiments confirm that the bulk composition of all films is homogeneous and that an optimized Ga doping of 3.9 at.% is obtained for a substrate bias of −100 V and deposition pressure of 0.51 Pa. It was also verified that films with lower electrical resistivity (2.6 × 10−3 Ω∙cm) have a hexagonal wurtzite structure with [001] preferred crystallographic direction. These transparent conductive oxide thin films have potential applications as electrodes in photovoltaics.